Contextual barriers of respectful workplace in nursing: A focused ethnography - Azadeh Nouri; Akram Sanagoo; Leila Jouybari; Fariba Taleghani (Wolters Kluwer Medknow Publications, 2021)
Background: Respectful relationship among nurses is an important influencing factor of positive work environment and nursing outcomes. Disrespectful interpersonal behaviors set the scene for an unpleasant and unhealthy workplace in nursing. This can be harmful to persons and their organization and affect health care outcomes. This study was designed in order to search for contextual barriers to respectful behaviors in the context of nursing. Materials and Methods: This study was a focused ethnography that was carried out in medical-surgical wards of Shahid Chamran Hospital in Isfahan in 2018-2019. The data collection method consisted of 140 h of participant observation and semi-structured interviews with 34 informants. The nformants comprised 29 nurses, 2 assistant nurses, a physician, and 2 patients who were selected by purposive sampling. The first author of the study made direct observations as an outsider. The data were analyzed by Spradley's method. Results: Three main categories and eight subcategories were obtained from data analysis that are as follows: 1) Personal self: challenges of perceived respect (negative self-concept, unpleasant feelings, and ineffective communication), 2) Organizational-based perceived disrespect (poor organizational climate, inadequate job condition, restrictive organizational structure), 3) Social self: challenges of showed respect (implicit social norms, cultural gap). Conclusions: Individual and social attitudes, interactive communication, and organizational factors are the contextual determinants of a respectful workplace in nursing. Consequently, improving self-concept and effective communication skills as well as adjust organizational conditions and value conceptualization in society may effect a respectful workplace in nursing.